2014
DOI: 10.2478/apbi-2013-0001
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Digestion of Waste Water from Hydrothermal Carbonization of Corn Silage

Abstract: This experimental work investigates anaerobic digestion of waste water from hydrothermal carbonization of maize silage comparing a continuously stirred-tank reactor (CSTR) and an anaerobic filter (AF). Both reactors were operated for 91 days at a constant organic loading rate of 1 g COD L -1 d . Consecutively lower degradation rates were assumed to be caused by a significant lack of sulfur and phosphorus due to a precipitation by ferrous iron. Over the whole time the AF proved to be more stable. Very small con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
115
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(119 citation statements)
references
References 17 publications
4
115
0
Order By: Relevance
“…So, despite higher energy potential, fresh digestate cannot be used directly as a solid fuel. It would need to be dried right after the digestion 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, despite higher energy potential, fresh digestate cannot be used directly as a solid fuel. It would need to be dried right after the digestion 20 .…”
Section: Discussionmentioning
confidence: 99%
“…However, HTL requires very high pressure (250 bar) compare to HTC (10-50 bar), which implies a high installation and operation costs than HTC. Again, the combination sequence of AD and HTC can be questioned as Wirth et al recently reported AD of HTC process liquid 20 . However, an effective AD depends on the sugar concentration in the feedstocks.…”
Section: Introductionmentioning
confidence: 99%
“…The wash-waters contain organic C and N whose concentration should be reduced prior to disposal. One possible way of removing the organic compounds of the wash water is to perform anaerobic treatment as is done with the HTC-process liquor (Wirth and Mumme 2013), and methane would be produced concomitantly.…”
Section: Nitrous Oxide Emissionsmentioning
confidence: 99%
“…Hydrothermal liquefaction (HTL) process converts wet biomass under subcritical temperature (280˚C -374˚C) and pressure (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) to aqueous, solid char and gaseous products wherein process conditions, catalyst and biomass feedstock dictate product composition, distribution and yield [1] [2]. We have reported sub-critical HTL of lignocellulosic biomass (LCB) using homogeneous acid (Ca and Ni nitrate) catalyst [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a continuous HTL reactor operation will likely face persistent challenge of wastewater disposal. Alternatives such as catalytic hydrothermal gasification [9], photoreforming for H 2 production [10], anaerobic digestion for methane production [11] have been investigated to recover organic components of the AP. Another route which is microbe mediated capture of AP carbon and nutrients is more appealing because it will simultaneously reduce the ) of organic carbon [22].…”
Section: Introductionmentioning
confidence: 99%